Description of the female and notes on distribution, habitat, nymphal development, song and chromosomes of Tropidonotacris grandis Ragge (Orthoptera: Phaneropteridae) - Hemp, Claudia; Heller, Klaus-Gerhard; Warchałowska-Śliwa, Elżbieta; Hemp, Andreas (Zootaxa, 2014)
The female of Tropidonotacris grandis is described and information on distribution, habitat, song, chromosomes and nymphal development of this species given. The populations of northern Tanzania all occur in deciduous dry forest, a habitat highly endangered by destruction and therefore T. grandis must be regarded at least as a vulnerable species according to the IUCN red list.